Nurturing the sustainable food systems: crafting policies and practices for crop diversification in Bangladesh - Nandi, Ravi; Krupnik, Timothy J.; Kabir, Wais; Jackson, Tamara (Frontiers in Sustainable Food Systems, 2024)
Bangladesh’s agriculture is highly rice-centric. Although economically rational, this is also risky, and arguably unsustainable. As a result, there is increasing interest in crop diversification (CD). This study examines the policy environment and the implementation of projects promoting CD in Bangladesh from 1971 to the present. An integrated analytical framework, developed by the International Wheat and Maize Improvement Center (CIMMYT) was used. Despite numerous policies and projects aimed at promoting CD, progress remains limited due to historical biases and various challenges. This research identifies a significant gap in existing approaches, which primarily focus on production aspects while neglecting market systems for new crops. Additionally, inadequate coordination among government agencies has impacted the effectiveness of projects implemented by development partners. The study highlights that CD efforts have been largely project-driven and short-lived, emphasizing the need for mainstreaming CD with dedicated annual funding to ensure long-term sustainability. Key challenges in funding, market development, and implementation are identified. The study recommends mainstreaming CD through annual budgets and enhancing market linkages. Furthermore, it provides actionable guidelines for policymakers and practitioners to effectively promote and sustain crop diversification in Bangladesh’s agriculture.